Effect of Rhodotorula glutinis yeast x mulberry leaves on morpho-productive characteristics of IBA polyvoltine breed of silkworm Bombyx mori L. - Alexandra M Bardoș-Marțiș; Mihaela Hăbeanu; Anca Gheorghe; Nicoleta A Lefter; Teodor Mihalcea (Scientific Papers Animal Science and Biotechnologies)
The mulberry leaves are the sole feed for the silkworm Bombyx mori L. The use of yeast has a great impact in the development of the morpho-productive parameters as shown in other studies and the results may differ by silkworm breed and the day of administration of the yeast. The objective of this study consists in evaluating the IBA silkworm performance, a polyvoltine breed, fed with mulberry leaves +/- Rodotorula glutinis yeast. The morpho-productive performances were determined during the trial in the 5th instar at 1st, 5th, 7th and 9th days. A total of 300 larvae were distributed randomly in 3 groups (100 larvae/group, 2 replicates each one): 1. C group fed mulberry leaves; 2. E1 fed C diet and yeast (1x107); 3. E2 fed C and yeast (1x109). Mulberry leaves treated with R. glutinis yeast, irrespective of concentration and days of measurements, had a positive influence on the morpho-productive parameters of IBA breed larvae (weight and average daily gain). The silk gland weight and cocoons traits (weight of the pupae, weight of raw cocoon and longitudinal and transversal axes) were superior in experimental diets.